Analysis of Cable Stayed Bridges for Flutter with Gyroscopic Active Control Device as Torsional Damper - Barath, Ragesh P M (My University, 2015)
Cable supported bridges are distinguished by their ability to overcome larges spans. At present cable supported bridges are enabled for spans in range from 200m to 2000m, thus covering approximately 90% of the present span range. Even though they have the huge advantage of covering the cost of construction of pylons in deep waters they are not without disadvantages. They high degree of indeterminacy which makes them tough for analysis and also the large spans makes them high susceptible to dynamic loading problems as they have high degree of freedom. Cable supported bridges have reached up to a span of 1991m in Akashi Kaikyo Bridge which is a cable suspended bridge and 1104m in Russky’s bridge which is a cable stayed bridge. These bridges have huge span to depth ratio which is the advantage of these bridges in architectural and economic point of view makes them susceptible to aerodynamic forces due to wind loads. The failure of Tacoma Narrows bridge in November 1940 at very low wind speed of only 64km/hr lead to the new field of wind engineering to be taken seriously. Various researches were done on various aerodynamic forces that would act on structures like along wind response, across wind response of structures, buffeting, vortex shedding, galloping, torsional divergence flutter etc. These researches led to ground breaking achievements in tall structures and long span bridges. With the improvement of heights of building and increasing problems occurred in dynamics of the building. To control the problems occurring in structures various control mechanisms were also introduced with respect to time. The Gyroscope is equipment that works with principle of “Law of conservation of angular momentum”. These are used for various purposes such as leveling instruments, balancing instruments, toys, aerospace industry, shipping etc. In shipping it used in anti roll gyroscopes which helps to reduce the discomfort caused by roll of ship which was caused by wave effect in ships. These equipments were used as early as 1850’s in passenger ships to give comfort to passengers. The idea of this project is to use this as the same principle as antiroll gyroscopes to provide torsional damping to the cable stayed bridges to protect the bridges from coupled or classic flutter and single degree of freedom flutter or torsional flutter in low wind velocities. By providing these dampers and increasing the flutter velocity we can increase the flutter velocity to 71.936 % to that of undamped flutter velocity while increasing the damping by 806.79% The increase in damping ratio might look huge but the damping ratio to the critical varies from 0.2% to 1.8% which is very less compared to normal R.C and steel structures which has damping ratios up to 5% without providing any additional damping device.
M.E. (Structural Engineering)
Keywords: flutter; cable stayed bridges; gyroscope; civil engineering; structural engineering; CED